2022
DOI: 10.12688/hrbopenres.13656.1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting perineal trauma during childbirth using data from a general obstetric population

Abstract: Background: Perineal trauma is a common complication of childbirth and can have serious impacts on long-term health. Few studies have examined the combined effect of multiple risk factors. We developed and internally validated a risk prediction model to predict third and fourth degree perineal tears using data from a general obstetric population. Methods: Risk prediction model using data from all singleton vaginal deliveries at Cork University Maternity Hospital (CUMH), Ireland during 2019 and 2020. Third/four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Mother and child characteristics of study participants who did and did not sustain a third/fourth degree tear are outlined in Table 1. Obstetric characteristics of study participants by parity and results of univariable analysis are shown in Tables A1 and A2 as Extended data 8 , with nulliparity, mode of delivery, increasing birthweight and post-term delivery significantly associated with an increased risk of third/fourth degree tears. These variables were used in the multivariable logistic regression with backward stepwise selection to develop the prediction model for third/fourth degree tears.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mother and child characteristics of study participants who did and did not sustain a third/fourth degree tear are outlined in Table 1. Obstetric characteristics of study participants by parity and results of univariable analysis are shown in Tables A1 and A2 as Extended data 8 , with nulliparity, mode of delivery, increasing birthweight and post-term delivery significantly associated with an increased risk of third/fourth degree tears. These variables were used in the multivariable logistic regression with backward stepwise selection to develop the prediction model for third/fourth degree tears.…”
Section: Resultsmentioning
confidence: 99%
“…There was little difference between the shape of the linear function for birthweight compared to the spline function using 3 and 4 knots, while 5 knots overfit the data (Figure A1, found as Extended data 8 ). The AIC and BIC statistics were lowest for the linear function; therefore, birthweight was analysed as a linear function.…”
Section: Model Performance and Internal Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the MN-CMS provides opportunity for new data-driven discovery to answer a broad range of research questions on maternal and child health 3 . For example, using anonymised MN-CMS data, we previously developed and validated prediction models examining a combination of risk factors to predict postpartum haemorrhage (PPH) and third-and fourth-degree perineal tears in a general obstetric population 4,5 . Additionally, other studies have used MN-CMS data to assess risk factors for antenatal pyelonephritis 6 , to examine the impact of an electronic health record on task time distribution in a Neonatal Intensive Care Unit 7 and to examine institutional rates of unsuccessful operative vaginal delivery in a tertiary level maternity hospital in Ireland 8 .…”
Section: Introductionmentioning
confidence: 99%